Strategic Management of Information Systems in the New Student Admission Process (PPDB) at an Islamic Senior High School 4 Aceh Besar - Hazal Fitri (Journal Informatic, Education and Management (JIEM), 2026)
In the era of globalization, technology has become a cornerstone of the educational landscape, necessitating that educational institutions adapt to digital advancements to enhance the effectiveness and efficiency of their systems. However, the management of websites for student recruitment often encounters significant obstacles, such as frequent technical errors and server downtime due to high traffic, a shortage of skilled human resources for web management, and limited infrastructure. This study aims to analyze the management of the school website as a medium for student recruitment and to identify the challenges and efforts involved in its implementation at MAN 4 Aceh Besar. This research employs a qualitative method with a descriptive approach. Data collection was conducted through interviews, observations, and documentation involving the research subjects. The findings indicate that the management of the recruitment website has been executed according to established procedures, encompassing planning stages, the formation of a team involving all school stakeholders, structured implementation, and routine evaluations to ensure website effectiveness. Despite these efforts, challenges remain, specifically technical errors and limitations in human resources and infrastructure. Nevertheless, the school continues to take proactive measures to overcome these hurdles, such as conducting training programs to enhance the competence of website administrators and upgrading infrastructure. These efforts are aimed at achieving the primary objectives for which the recruitment website was initially developed.